TRADITIONAL HORSERACING AND SPORT GAMES OF KAZAKHS AND KIRGHIZ IN THE 19TH AND THE BEGINNING OF 20TH CENTURIES - Kalysh, A.; Asankanov, A. (Journal of history, 2018)
Article is devoted to traditional horse-racing games of 19th – the beginnings of the 20th centuries which take the important place in national history of the Kazakhs. Among them the military-sport games connected as with military life (wars, attacks, collisions), and with economic activity of society enjoyed special popularity. Such games were sajys, audaryspak, zhamby atu, horse races, etc. Their genesis goes back to antiquity and the Middle Ages and in them such peculiar phenomena as sport, military skills, cult representations and magic actions were reflected, having similarity to similar games of the people of Central Asia, the Caucasus, the Volga region and Altai. In no small measure it was promoted also by that circumstance that many of them have arisen in the nomadic environment and the subject, the place and time of carrying out reflected features of outlook, economic and cultural activity and material culture both nomads cattle-farmers, and settled farmers. At the same time games and entertainments carried out always and public functions, such as educational, military and sports, ritual, spectacular and esthetic, communicative, etc.